2020
DOI: 10.1007/s40744-020-00223-6
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Screening for Celiac Disease in Systemic Lupus Erythematosus: A Single Experience of a Tertiary Medical Center

Abstract: Introduction: Systemic lupus erythematosus (SLE) is a multi-organ inflammatory disease associated with autoimmune diseases. The aim of the study is to assessed the frequency of celiac disease (CD) in adults and children with SLE (aSLE and cSLE, respectively) and compare them with rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) patients; the study also explored the clinical impact of CD serologic markers on SLE disease activity and severity. Methods: This was a cross-sectional study. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Unfortunately, these three pediatric studies included small cohorts of patients, and the screening approach was quite variable. Overall, none showed a potential increase in CD prevalence in pSLE patients [26,55,56].…”
Section: Pediatric Systemic Lupus Erythematosus and Celiac Diseasementioning
confidence: 91%
See 3 more Smart Citations
“…Unfortunately, these three pediatric studies included small cohorts of patients, and the screening approach was quite variable. Overall, none showed a potential increase in CD prevalence in pSLE patients [26,55,56].…”
Section: Pediatric Systemic Lupus Erythematosus and Celiac Diseasementioning
confidence: 91%
“…In order to investigate the epidemiological burden of CD in JIA patients, the literature search was performed using PubMed with the keywords (["children"] AND "Celiac Disease" AND "arthritis" OR "Juvenile Idiopathic Arthritis") restricted between 2000 and 2021 (31 December). Only the clinical studies describing cohorts (not case reports or series) of JIA patients screened for CD were included for data extraction, as summarized in Table 1 [15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Juvenile Idiopathic Arthritis and Celiac Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The present study still found that 9.6% of the subjects tested positive for anti-gliadin antibodies (either AGAG or AGAA), 3.5% for TGA and 2.6% for EMA. The negative impact of the lack of screening resides in the possibility of incorrect diagnosis and management, which can lead to unnecessary exposure to immunosuppressive drugs associated with side effects [11].…”
Section: Epidemiologymentioning
confidence: 99%